Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/cmdc.201600426
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments Using Small Molecules to Target RAD51: How to Best Modulate RAD51 for Anticancer Therapy?

Abstract: Homologous recombination (HR) is an evolutionarily conserved DNA repair process. Overexpression of the key HR protein RAD51 is a common feature of malignant cells. RAD51 plays two distinct genome-stabilizing roles, including HR-mediated repair of double-strand breaks (DSBs) and the promotion of replication fork stability during replication stress. Because upregulation of RAD51 in cancer cells can promote tumor resistance to DNA-damaging oncologic therapies, we and others have worked to develop cancer therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…Low activity can yield genome instability through defects in fork protection and HDR, but it also improves the cell killing by chemotherapeutics and PARP inhibitors (Budke et al, 2016; Quiros et al, 2011). On the other hand, RAD51 overexpression causes genome instability (Klein, 2008; Richardson et al, 2004), and RAD51 is frequently overexpressed in cancers (Klein, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Low activity can yield genome instability through defects in fork protection and HDR, but it also improves the cell killing by chemotherapeutics and PARP inhibitors (Budke et al, 2016; Quiros et al, 2011). On the other hand, RAD51 overexpression causes genome instability (Klein, 2008; Richardson et al, 2004), and RAD51 is frequently overexpressed in cancers (Klein, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Second, inhibiting the central, but not the initial step in HR, after the DSB is committed to be repaired through a homology directed mechanism prevents it from repair by NHEJ. Finally, RAD51 overexpression has been observed in a range of different cancers, and the associated resistance to radiation and chemotherapy was overcome by reduction in RAD51 expression (reviewed in (Klein, 2008) and (Budke et al, 2016)).…”
Section: Modulators Of the Rad51 Recombinasementioning
confidence: 99%
“…Rad51 overexpression leads to the accumulation of abnormal karyotypes and gene mutations, which are closely related to carcinogenesis and drug resistance [16]. Studies have shown that, such as breast cancer, pancreatic cancer and other tumors overexpressed Rad51 protein, positively correlated to tumor histological grade and stage [17,18]. In addition, domestic and foreign researchers also found that gene polymorphism of Rad51 recognized as the risk factor of CRC carcinogenesis.…”
Section: Discussionmentioning
confidence: 98%